Above-knee amputation due to necrotizing fasciitis caused by a gas-producing strain of Escherichia coli and negative pressure therapy assisted closure of a large open wound - Pešić, Slobodan; Tulenčić Egić, Snežana; Zwick, Mihajlo (Vojnosanitetski pregled, 2023)
Introduction. Nonclostridial gas-forming soft tissue infections (NGSTI) are rare, rapid progressive infections characterized by high mortality and high amputation rates. Surgical debridement is crucial in therapy, and it results in complex wounds that need to be closed in order to prevent secondary morbidity. Case report. Herein we present a case of NGSTI in a 68-year-old diabetic patient with acute thrombosis of popliteal artery aneurysm and radiological signs of gas in his right leg and the urinary bladder wall. The infection was caused by a gas-forming strain of Escherichia coli. In the early stage of the disease, the patient was treated with antibiotics and femoral amputation. A vacuum-assisted closure (VAC) treatment was applied to close the amputation wound. Administered VAC therapy resulted in primary wound closure without complications 17 days after surgery. Conclusion. Negative pressure increases the clearance of fluid and infection from the wound but also increases wound contraction and approximation of skin flaps.  To avoid extensive reconstructive surgery, VAC therapy can be a good adjunctive treatment for closing large open wounds in patients with NGSTI.
Keywords: amputation, surgical; diabetes mellitus; escherichia coli; necrotizing fasciitis